Sphingomyelin biosynthesis: its impact on lipid metabolism and atherosclerosis. (October 2009) - Jiang, Xian-Cheng; Yeang, Calvin; Li, Zhiqiang; Chakraborty, Mahua; Liu, Jing; Zhang, Hongqi; Fan, Yifan
The ability to regulate sphingomyelin (SM) biosynthesis could become a promising treatment for atherosclerosis. SM is one of the major lipid components in plasma and cell membranes. We have found that plasma SM level is an independent risk factor for coronary artery disease. Thus, SM levels have a clinically important impact on lipoprotein metabolism. We have also found that reduction of plasma and liver SM, with concomitant reduction of atherosclerosis, could be achieved by pharmacological inhibition of serine palmitoyltransferase in a mouse model. Moreover, we also found SM synthase 2, the last enzyme for SM biosynthesis, deficiency in macrophages decreases SM levels on plasma membrane and, thus, decreases atherosclerosis in a mouse model. These observations emphasize the need for a better understanding of SM metabolism. This review mainly focuses on the relationship between SM de novo synthesis, lipid metabolism and atherosclerosis.